Formation of Sharia Entrepreneurship ValuesIn Boarding Schools - Dwi Widyastuti, Reni; Febriati, Febriati; Afif, Ali (Green Publisher Indonesia, 2022)
This study intends to determine the method of developing the values of independence of the students of Mu'Inul Islam Kubu Raya Islamic boarding school. This type of research is qualitative research, with primary data sources, namely data obtained directly from the object of research, namely the Mu'Inul Islam Kubu Raya boarding school and secondary data sources in the form of articles and research reports) and interviews. Data was collected through observation, interviews and documentation. The collected data were then analyzed using descriptive analytical methods. The results showed: the Islamic boarding school method in developing the independence values of Mu'Inul Islam Kubu Raya students is based on the philosophy of gusjigang (a good boy, good character, good at reciting the Koran, good at trading) Sunan Kudus, the process is carried out using observation methods, practical methods, theoretical studies, motivation, facilitation, and exemplary. It can be seen from an Islamic economic perspective, the method for developing the values of independence of students at the Mu'Inul Islam Kubu Raya Islamic boarding school is taken from the values of Islamic teachings about entrepreneurship contained in the Koran, hadith and the life practices of the Prophet Muhammad SAW. the process is carried out using observation methods, practical methods, theoretical studies, motivation, facilitation, and exemplary. It can be seen from an Islamic economic perspective, the method for developing the values of independence of students at the Mu'Inul Islam Kubu Raya Islamic boarding school is taken from the values of Islamic teachings about entrepreneurship contained in the Koran, hadith and the life practices of the Prophet Muhammad SAW. the process is carried out using observation methods, practical methods, theoretical studies, motivation, facilitation, and exemplary